Class and Structural Inequality of fishing communities in Ambon City - Attamimi, Gadri Ramadhan; Kinseng, Rilus A; Agusta, Ivanovich (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
Social class is a social phenomenon that often occurs in every social group including the fishing communities. The structural inequality of fishing communities is characterized by the imbalance in ownership of production equipment and income distribution among fishermen. This research was conducted in one of the Fishermen Village (Negeri) in Ambon City, called Negeri Latuhalat. Type of research used in this study is post-positivism paradigm using qualitative approach supported by quantitative research. The purpose of this research is to analyze the level of imbalance between Ambon City fishermen. The results showed the formation of fishermen social classes which consist of masnait fishermen, tanase fisherman laborer, small fishermen, middle fishermen and tenant fisherman (capitalist). The gini index of fishermen in the research location shows a figure of 0.74, meaning that it shows a high imbalance between fisherman classes. The ratio of kuznets or the average comparison between fishermen received by 33% of the top group of Rp. 8,404,567, - and 25% of the lowest group of Rp. 2.040.000, -. Measurements using the World Bank also show the same thing with the results of gini index measurements that illustrate the portrait of inequality income distribution in the study sites. This condition illustrates that there has been an imbalance between fishermen classes, as much as 75% are only able to receive 8.72% of total income while as much as 25% of tenant fishermen (capitalist) enjoy and control 91.73% of total income.